PENGARUH KOMPETENSI, INTEGRITAS, OBJEKTIVITAS, DAN PENGALAMAN KERJA TERHADAP KUALITAS HASIL PEMERIKSAAN - Anggita Dian Krismadani; Hustianto Sudarwadi; Camelia Lusandri Numberi (Cakrawala Management Business Journal, 2022)
The purpose of the study was to obtain empirical evidence regarding the effect of competence, integrity, objectivity, and work experience on the quality of an auditor's examination results. This research was conducted on auditors and examiners within the government, namely the Inspectorate Office of Manokwari Regency and the Inspectorate Office of West Papua Province. The population in this study were all auditors at the Inspectorate Office of Manokwari Regency and the Inspectorate Office of West Papua Province, totaling 40 auditors. The sampling technique in this research is saturated sampling by taking all members of the population as the research sample. The analysis used in this study was multiple linear regression analysis which was processed using the SPSS version 22 program. The results showed that only the objectivity variable had an effect on the quality of the examination results. The variables of competence, integrity, and work experience have no effect on the quality of the examination results. Keywords: Competence, Integrity, Objectivity, Work Experience, Quality of Examination Results.